ENHANCING BEGINNER VOCABULARY THROUGH THE POWER OF SONGS - Abbas, Alaa Abdul Adheem Abdul; Muslim, Afrah Mohammed; Enad, Aseel Ubaiss (PT. Antis International Publisher, 2025)
Objective: The objective of this research was to investigate the effectiveness of using songs as a method to teach vocabulary. It aimed to address the challenges faced by beginner students, such as memory issues, vocabulary retention, incorrect pronunciations, and lack of context. Method: The study was conducted on 25 beginner students from Toah Al-Mouradia Primary School in Iraq-Najaf. Additionally, a questionnaire was given to ten teachers from various primary schools in Najaf and Diwaniyah. Both tools were used to collect data. Results: The research findings indicated that songs can be used as an effective pedagogical tool to teach vocabulary. The experiment showed positive results when songs were incorporated in the classroom. Furthermore, Iraqi primary school teachers believe that songs can provide young learners with opportunities to practice, learn, and retain vocabulary. These findings support the use of songs as a valuable tool to enhance young learners' vocabulary proficiency. Novelty: Therefore, songs should be used more often in Iraqi schools, as this research proved it to be a sustainable pedagogical tool for beginner vocabulary learners.